Analysis of the Causes of Drop out among Girls’ Students in Balochistan - Baloch, Shah Khalid; Brohi, Dr. Ahmed Ali; Zehri, Abdul Wahid (Hanken, 2015)
In fact drop out from school among girls is a universal issue. In most countries girls drop out from school for various reasons such as socio- economic factors, early marriages, school related factors, pregnancy, religious factors, cultural factors and ailing health. The aim of this study is to identify why girls drop out from school in Balochistan. An interview schedule was used in collecting data from the respondents. 100 respondents were non-randomly selected from a pool of girl’s primary and secondary schools in Quetta city, in this regard twenty primary schools and twelve secondary schools were selected for study. Data was analyzed using percentages. The main reasons and factors of drop out from school among girls students in Balochistan revealed from the results of the study are poverty, distance from home to school, poor health, early marriages, non- availability of educational facilities, lack of parents interest, teachers violent behavior and difficult curriculum. The findings of the study may help to policy makers, planners of education department, teachers and parents to take serious actions for controlling drop out and increasing enrollment rate specifically at the primary and secondary level in Balochistan.